Quantifying forward guidance and yield curve control - Junko Koeda; Bin Wei (Federal Reserve Bank of Atlanta, 2024)
This study evaluates the effectiveness of Japan's unconventional monetary policies over the past quarter century within a unified term structure framework. It specifically examines the impact of the Bank of Japan's (BOJ) outcome-based forward guidance and yield curve control (YCC) and incorporates other policy types into the framework. The findings show that the BOJ's forward guidance and YCC have both had a significant impact on the shadow rate. Forward guidance accounted for most of the policy impact in the early stages of unconventional monetary policies and remained influential throughout. YCC, since its introduction in 2016 until March 2022, contributed to more than a third of the policy impact. Furthermore, these policies have been effective in raising output and inflation.
Keywords: E43; E44; E52; E58; 330; forward guidance; effective lower bound (ELB); liftoff; term structure; shadow rate; macro finance; unspanned macro factors; yield curve control; Japan